Skryté výzvy ekofeminismu - Zora Javorská (Gender a Výzkum, 2010)
This article identifies connections between the current critical condition of nature and women’s position in society. The author describes ecofeminism and situates it within the context of the feminist and environmental movements. The purpose of this article is to introduce the fundamental ideas of ecofeminism, whose underlying principle is a critique of dualistic thinking, and a critique of the application of the logic of dominance and hierarchy. The author argues how this critique is derived from feministic epistemology and goes on to explain the ecofeminist critique of dualistic thinking and hierarchy historically connected to the scientific revolution, which had a big impact on the position of women in society and the current global ecological crisis.